Answer:
d) a1 = 8, an = 2a(n-1)
Step-by-step explanation:
Let's see the first 3 terms of the sequence
![\begin{gathered} a_n=8(2)^(n-1) \\ a_1=8(2)^(1-1)=8(2)^0=8 \\ a_2=8(2)^(2-1)=8(2)^1=8(2)=16 \\ a_3=8(2)^(3-1)=8(2)^2=8(4)=32 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g4nrnhww5zvpt3l4crumrevqfsfnl36t1a.png)
Therefore, the first term is a1 = 8
And the next terms are twice the term before, we get
a2 = 2(8) = 16
a3 = 2(16) = 32
Then, the recursive formula is equal to
d) a1 = 8, an = 2a(n-1)